Uji Toksisitas Akut Limbah Cair Kelapa Sawit Terhadap Ikan Patin (Pengasius Sp) Dengan Metode Renewal Test - Queen Destya; Shinta Elystia; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Wastewater produced from palm oil industry could potentially cause pollution because it contains the value of COD and high organic matter that can effect the death of aquatic biota. Wastewater from the outlet Waste Treatment Unit PT. X is still above the quality standards set by the government. Therefore research on acute toxicity test of palm oil industry to determine the value of LC50 and to analyze the relationship of wastewater from the outlet Waste Treatment Unit PT. X towards the experimental animal. This research was done by renewal test method in 96 hours of observation by using Catfish (Pangasius sp.) as the test animals. LC50 value was calculated by probit method which utilized the catfish mortality and the parameters tested was DO, pH, temperature, COD,ammonia and nitrate. The characteristic value of wastewater of palm oil PT. X is COD 1426,8 mg/l, ammonia 0,9909 mg/l, nitrate 0,0075 mg/l, pH 8, DO 3 mg/l, and temperature 28°C which the parameter of COD passed the quality standar of the Environment Minister’s decision No. 51/MENLH/10/1995 about the Quality Standart of Waste Water for Palm Oil Industry. The result showed the value of LC50 is 9,878% and TUa (Toxicity Unit Area) of palm oil industrial wastewater is 10,22 showed that the wastewater of palm oil could make great acute toxicity.Keywords: catfish, palm oil wastewater,the value of LC50, renewal test.